Subculture's Not Dead! Checking the Pulse of Subculture Studies through a Review of 'Subcultures, Popular Music and Political Change' and 'Youth Cultures and Subcultures: Australian Perspectives'. (February 2019) - Williams, J. Patrick
Empirical studies of youth cultures and subcultures continue to flourish alongside active theoretical progression and debates within and across a variety of intellectual traditions. Annually, a range of published articles, monographs and edited collections improve our collective knowledge about youth (sub)cultural phenomena from nearly every corner of the globe. In this article I review two recent edited volumes that deal explicitly with subculture studies: The Subcultures Network's Subcultures, Popular Music and Political Change (2014, Cambridge Scholars Publishing) and Baker, Robards and Buttigieg's Youth Cultures and Subcultures: Australian Perspectives (2015, Ashgate). I provide a brief description and summative evaluation of each volume and then organize the review itself in terms of a set of topics that I find to be most salient across the many chapters: identity and identification, centre and periphery, social media, and history. The review moves back and forth between the two volumes as I bring together chapters that are conceptually or analytically similar. My goal is not only to review the significance of the various published studies, but to highlight the continued relevance of the subculture concept.